Defining Challenge Based Learning and Education in the Autonomous Shipping Context - Sandell, Peter; Salokannel, Johanna; Morariu, Andrei-Raoul; Tsvetkova, Anastasia; Bolbot, Victor; Saarni, Jouni; Isoaho, Jouni; Virtanen, Seppo (Sweden, 2026)
The increasing digitalization and introduction of Maritime Autonomous Surface ships (MASS) is changing the role of seafarers and other professionals in the maritime sector. The technological complexity of ships due to automation requires the development of skills related to, for example, cybersecurity, ship equipment engineering, and software development. This results in a demand for strong problem-solving abilities, adaptability to technological changes, and continuous learning, which, in turn, requires maritime education and training to become more adaptive and responsive. This includes emphasizing lifelong learning, embracing an interdisciplinary approach, and promoting project-based and problem-solving learning methods. Challenge-based learning has been established as a successful method for delivering practical real-world learning experiences in engineering disciplines and it has been proposed as an evolution of the Conceive, Design, Implement and Operate (CDIO) framework adopted widely in universities giving engineering education. In this paper, we present concrete definitions for the concepts of challenge-based learning and education in the MASS context. Such definitions for MASS education have not been previously presented in the literature. The definitions will pave the way for successfully applying challenge-based learning in this field and serve as foundations for building educational frameworks for MASS.
21st International CDIO Conference Proceedings - Full Papers